The settlement procedure in EC cartel cases: An empirical assesment - Kai Hüschelrath; Ulrich Laitenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In June 2008, the European Commission (EC) was enabled to introduce a settlement procedure that aims at promoting the procedural efficiency of cartel enforcement in the European Union (EU). We use a data set consisting of 84 cartels decided by the EC from 2000 to 2014 to empirically investigate the impact of the EU settlement procedure on the duration of cartel investigations. Separating the enforcement process into two consecutive stages, we find that the introduction of the settlement procedure is followed by a substantial shortening of the second stage - reaching from the statement of objections (SO) to the decision - while it leaves the duration of the first stage from the beginning of the case to the SO unaffected. Subsequent to a discussion of further evaluation approaches we conclude that the EU Settlement Procedure has increased procedural efficiency of cartel enforcement in the European Union substantially.
Keywords: K21; L41; 330; competition policy; cartels; settlements; ex-post evaluation; European Union